Mekanisme Pertahanan Diri Tokoh Matara dalam Novel Mata di Tanah Melus Karya Okky Madasari : Kajian Psikologi Sastra - Sandri, Mery; Indrastuti, Novi Siti Kussuji (Humanis, 2024)
This research aims to describe the aspects identified as a form of self-defense mechanism that occurs in the main character Matara in the novel "Mata Di Tanah Melus" by Okky Madasari. This research is studied using Sigmund Freud's thoughts on self-defense mechanisms. According to Freud, self-defense mechanisms are efforts from the subconscious to defend themselves from threats or anxiety. To describe the findings, this research uses a qualitative descriptive method. The results of this study show that there are four forms of self-defense mechanisms in Matara's character when facing conflict, namely: denial self-defense mechanism, repression self-defense mechanism, formation reaction self-defense mechanism, and rationalization self-defense mechanism. All forms of self-defense mechanism responses that occur in Matara's character are Matara's efforts to regain her comfort when she is in a situation that makes her anxious.